Ethics, history, politics and community in Martin Buber's myth of Zion - Breslauer, Daniel (Journal of Jewish studies, 2018)
Martin Buber's ideal of Zion has been criticized, especially by Dan Avnon, as lacking political realism and as a 'mismeeting' of biblical, theological and political concerns. This article examines how Buber's view of ethics, history and politics helped him describe a 'living centre' around which an organic and diverse community in which what has been called 'blended selves' could arise. Buber uses a biblical analysis similar to that of Spinoza, a historical approach that opposes historicism, and a politics of preparation rather than practical success to draw on a variety of Jewish sources to make a case that not only have Jewish communities in the past illustrated his ideal but that it is also possible in the current crisis dividing Israelis and Palestinians.